Impact Covid-19: Potret Transformasi Pendidikan melalui Pembelajaran Daring di Kecamatan Maesan, Bondowoso - Laili Istiqomah; Azwar Habibi (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2021)
The Covid-19 pandemic has had a major impact on various sectors, one of which is education. The world of education also feels the impact. Educators must ensure teaching andlearning activities continue, even though students are at home. It is hoped that the status ofa pandemic will pass quickly with increasing public awareness to join and break the chainof spreading this virus. This dedication article will address two issues; First, trying to lookat the problems of parents and school-age children during the pandemic in terms of education; Second, trying to build public awareness to prevent Covid-19. The results of this service are: First, providing solutions to parents and school-age children for problems that arise in the midst of a pandemic in the aspect of education; Second, increase public understanding of Covid-19 and how to prevent it. Keywords: Impact Covid-19, Educational Transformation, Online Learning. Abstrak Pandemi Covid-19 berdampak besar pada berbagai sektor, salah satunya pendidikan. Dunia pendidikan juga ikut merasakan dampaknya. Pendidik harus memastikan kegiatan belajar mengajar tetap berjalan, meskipun peserta didik berada di rumah. Status pandemi diharapkan cepat berlalu dengan peningkatan kesadaran masyarakat untuk ikut andil memutus mata rantai penyebaran virus ini. Artikel pengabdian ini akan membahas dua masalah; Pertama, mencoba untuk mengetahui problematika orang tua dan anak usia sekolah di saat pandemi dalam aspek pendidikan; Kedua, mencoba membangun kesadaran masyarakat untuk pencegahan virus Covid-19. Hasil dari pengabdian ini adalah: Pertama, memberikan solusi pada orang tua dan anak usia sekolah atas problematika yang muncul di tengah pandemi dalam aspek pendidikan; Kedua, meningkatkan pemahaman masyarakat tentang Covid-19 dan cara pencegahannya. Kata Kunci: Impact Covid-19, Transformasi Pendidikan, Pembelajaran Daring.